Targeted deep sequencing of cell‐free DNA in serous body cavity fluids with malignant, suspicious, and benign cytology. Issue 1 (21st November 2019) - Yang, Soo‐Ryum; Mooney, Kelly L.; Libiran, Paolo; Jones, Carol D.; Joshi, Rohan; Lau, Hubert D.; Stehr, Henning; Berry, Gerald J.; Zehnder, James L.; Long, Steven R.; Kong, Christina S.; Kunder, Christian A.
Abstract : Background: Liquid biopsy using cell‐free DNA (cfDNA) presents new opportunities for solid tumor genotyping. While studies have demonstrated the utility of cfDNA from plasma, cfDNA from other body fluids remains underexplored. Methods: We evaluated the molecular features and clinicopathologic correlates of cfDNA from serous body cavity fluids by performing hybrid capture‐based next‐generation sequencing (NGS) on cfDNA isolated from residual effusion supernatants. Twenty‐one serous effusions from pleural (n = 15), peritoneal (n = 5), and pericardial (n = 1) cavity were analyzed. Results: The supernatants provided a median cfDNA concentration of 10.3 ng/µL. Notably, all effusions were sequenced successfully to a median depth >1000×, revealing a broad range of genetic alterations including single nucleotide variants, small insertions and deletions, amplifications, and fusions. Specifically, pathogenic alterations were identified in all malignant fluids (13/13), all fluids suspicious for malignancy (2/2), and 1 benign fluid (1/6) from a patient with metastatic cancer. To validate our findings, we examined matching results from 11 patients who underwent additional testing using formalin‐fixed, paraffin‐embedded (FFPE) specimens. In 8 patients, the paired results between FFPE and supernatant testing were concordant, whereas in the remaining 3 patients, supernatant analysis identified additional variants likely associated with resistance to targeted therapies. Additional comparison between FFPE and supernatant testing showed no difference in DNA concentration ( P  = .5), depth of coverage ( P  = .6), or allele frequency of pathogenic mutations ( P  = .7). Conclusion: cfDNA isolated from serous body cavity fluids represents a promising source of genomic input for targeted NGS. Abstract : We performed targeted next‐generation sequencing on cell‐free DNA isolated from serous body cavity fluids. By applying cell‐free DNA testing to residual effusion supernatants, our custom liquid biopsy allows for robust detection of clinically actionable genetic alterations from routinely discarded material and may serve as a potential alternative to formalin‐fixed, paraffin‐embedded specimens in select patients.